Apparent diffusion coefficient of normal adrenal glands - Teixeira,Sara Reis (2016)
Abstract Objective: To assess the feasibility and reliability of apparent diffusion coefficient (ADC) measurements of normal adrenal glands. Materials and methods: This was a retrospective study involving 32 healthy subjects, divided into two groups: prepubertal (PreP, n = 12), aged from 2 months to 12.5 years (4 males; 8 females); and postpubertal (PostP, n = 20), aged from 11.9 to 61 years (5 males; 15 females). Diffusion-weighted magnetic resonance imaging (DW-MRI) sequences were acquired at a 1.5 T scanner using b values of 0, 20, 500, and 1000 s/mm2. Two radiologists evaluated the images. ADC values were measured pixel-by-pixel on DW-MRI scans, and automatic co-registration with the ADC map was obtained. Results: Mean ADC values for the right adrenal glands were 1.44 × 10-3 mm2/s for the PreP group and 1.23 × 10-3 mm2/s for the PostP group, whereas they were 1.58 × 10-3 mm2/s and 1.32 × 10-3 mm2/s, respectively, for the left glands. ADC values were higher in the PreP group than in the PostP group (p < 0.05). Agreement between readers was almost perfect (intraclass correlation coefficient, 0.84-0.94; p < 0.05). Conclusion: Our results demonstrate the feasibility and reliability of performing DW-MRI measurements of normal adrenal glands. They could also support the feasibility of ADC measurements of small structures.